Dynamic multi-phase partitioning of decamethylcyclopentasiloxane (D5) in river water - Whelan, Michael J.; van Egmond, Roger A.; Gore, David; Sanders, David A. (Elsevier, 2010)
The behaviour of decamethylcyclopentasiloxane (D5) in river water was evaluated by measuring concentration changes in open beakers. Effective values for the partition coefficient between organic carbon and water (K) were derived by least-squares optimisation of a dynamic model which accounted for partitioning between the sorbed and dissolved phases of D5, and for losses via volatilisation and hydrolysis. Partial mass transfer coefficients for volatilisation were derived from model fits to controls containing deionised water. Effective values of log (K) were between 5.8 and 6.33 (mean 6.16). These figures are higher than some other experimentally-derived values but much lower than those estimated from the octanol: water partition coefficient using single-parameter linear free energy relationships (LFERs). A poly-parameter LFER gave a predicted log (K) of 5.5. Differences in partitioning are believed to be due to the nature of the organic matter present. The new value for effective K was employed in a simple model of D5 behaviour in rivers to ascertain the extent to which a higher affinity for organic carbon would depress volatility. The results suggest that despite the revised K value, volatilisation of D5 remains a significant removal mechanism in surface waters. © 2010 Elsevier Ltd